Wide temperature operation of diamond quantum sensor for electric vehicle battery monitoring - Kubota, Keisuke; Hatano, Yuji; Kainuma, Yuta; Shin, Jaewon; Nishitani, Daisuke; Shinei, Chikara; Taniguchi, Takashi; Teraji, Tokuyuki; Onoda, Shinobu; Ohshima, Takeshi; Iwasaki, Takayuki; Hatano, Mutsuko (Diamond and related materials, 2023)
Considering the rising popularity of electric vehicles (EVs), it is essential to enhance the cruising mileage and extend the lifetime of batteries. To accomplish this, accurate monitoring of the charge and discharge current of the battery over a wide temperature range is essential. We developed a compact diamond quantum sensor head with a size of 1 × 1 × 0.5 cm3, consisting of a (111) high-pressure and high-temperature synthesized diamond with nitrogen-vacancy centers, by electron beam irradiation, which was adhered to the top of the multimode fiber and surrounded by the microwave antenna, for EV battery monitoring. We demonstrated that our quantum sensor achieved the current measurement accuracy of 10 mA in the −150 to 150 °C temperature range with a bandwidth of 500 Hz under atmospheric pressure and confirmed that the diamond quantum sensor meets the performance requirements of EV current sensors. Moreover, the temperature dependence of shot noise and external magnetic field noise were investigated, and their relation to the linewidth and contrast of the optically detected magnetic resonance spectrum were analyzed. At high temperatures, the contrast decreased because shortening of the singlet lifetime, which accelerate the initialization. At low temperatures, the contrast was slightly decreased. This is possibly a result of increased losses due to condensation on the microwave antenna. [Display omitted] •A compact diamond quantum sensor with a size of 1 × 1 × 0.5 cm3 was developed.•Stable operation of diamond quantum sensors was shown in −150–150 °C.•Current measurement accuracy of 10 mA with a bandwidth of 500 Hz was confirmed.•The sensor exceeds the performance requirements of EV sensors was confirmed.